Drinking in transition: trends in alcohol consumption in Russia 1994-2004 - Perlman Francesca JA (BMC, 2010)
Abstract Background Heavy alcohol consumption is widespread in Russia, but studying changes in drinking during the transition from Communism has been hampered previously by the lack of frequent data. This paper uses 1-2 yearly panel data, comparing consumption trends with the rapid concurrent changes in economic variables (notably around the "Rouble crisis", shortly preceding the 1998 survey round), and mortality. Methods Data were from 9 rounds (1994-2004) of the 38-centre Russia Longitudinal Monitoring Survey. Respondents aged over 18 were included (>7,000 per round). Trends were measured in alcohol frequency, quantity per occasion (by beverage type) and 2 measures of potentially hazardous consumption: (i) frequent, heavy spirit drinking (≥80 g per occasion of vodka or samogon and >weekly) (ii) consuming samogon (cheap home-distilled spirit). Trends in consumption, mean household income and national mortality rates (in the same and subsequent 2 years) were compared. Finally, in a subsample of individual male respondents present in both the 1996 and 1998 rounds (before and after the financial crash), determinants of changes in harmful consumption were studied using logistic regression. Results Frequent, heavy spirit drinking (>80 g each time, ≥weekly) was widespread amongst men (12-17%) throughout, especially in the middle aged and less educated; with the exception of a significant, temporary drop to 10% in 1998. From 1996-2000, samogon drinking more than doubled, from 6% to 16% of males; despite a decline, levels were significantly higher in 2004 than 1996 in both sexes. Amongst women, frequent heavy spirit drinking rose non-significantly to more than 1% during the study. Heavy frequent male drinking and mortality in the same year were correlated in lower educated males, but not in women. Individual logistic regression in a male subsample showed that between 1996 and1998, those who lost their employment were more likely to cease frequent, heavy drinking; however, men who commenced drinking samogon in 1998 were more likely to be rural residents, materially poor, very heavy drinkers or pessimistic about their finances. These changes were unexplained by losses to follow-up. Conclusions Sudden economic decline in late 1990s Russia was associated with a sharp, temporary fall in heavy drinking, and a gradual and persistent increase in home distilled spirit consumption, with the latter more common amongst disadvantaged groups. The correlation between heavy drinking and national mortality in lower educated men is interesting, but the timing of RLMS surveys late in the calendar year, and the absence of any correlation between drinking and the subsequent year's mortality, makes these data hard to interpret. Potential study limitations include difficulty in measuring multiple beverages consumed per occasion, and not specifically recording "surrogate" (non-beverage) alcohols.